Effect Of Product Quality On Customer Loyalty In Bakso Baper In Gowa District - Andi Muh Israq Burhanuddin; Firman Umar; Andi Aslinda; Muh Rivai (Pinisi Business Administration Review, 2021)
This study discusses the Effect of Product Quality on Customer Loyalty. In this study, researchers tried to determine whether Product Quality has an influence on Customer Loyalty. This research is a quantitative study using a survey method. The data was collected by means of a questionnaire and analyzed using a statistical formula, namely Simple Linear Regression Analysis, which is calculated using SPSS assistance. The results of this study are that there is an influence between Product Quality and Customer Loyalty, with a value of 0.990.